Electrical Measuring Techniques — Expectations for Increasing Accuracy - Matiss, Imants; Purvinsh, Andris (Electrical, Control and Communication Engineering, 2010)
Multi parameter testing by Calibrated Disturbing Factors (CDF) methodology may present interest as more sophisticated mean for increasing metrological qualities of electrical testing techniques. Detailed analysis of a set of validation parameters, such as thickness and dielectric permeability of plates, demonstrates advantage of this approach in comparison with single parameter tests.